Measures of Bayesian Reasoning Performance on 'Normal' and 'Natural' Frequency Tasks. Issue 3 (2nd July 2016) - Stock, Rosemary; Fisk, John E.; Montgomery, Catharine
ABSTRACT: While the majority of similar studies examining Bayesian reasoning investigate how participants avoid common errors such as base-rate neglect, the current research also examines whether different formats (frequency and probability) lead to a difference in levels of absolute accuracy. In Study One, older (≥60 years) and younger (18 to 29 years) participants completed tasks in probability and normalized frequency formats. In Study 2, participants completed tasks in probability and natural frequency formats. Findings are that frequencies lead to less over-estimation, particularly in natural frequency tasks, which also reveal an interaction between age and task format whereby older adults seem unaffected by format. There was no association found between format and the avoidance of errors such as base-rate neglect. Findings are discussed in the light of dual and multi-process theories of reasoning, having failed to support the theory that frequency formats elicit System 2 reasoning processes.